Role of Physics Student Worksheet Integrated PBL Model to Improve the 21st Century: A Systematic Literature Review - Sharvina Salsabil; Pakhrur Razi; Hufri Hufri; Dea Stivani Suherman (Jurnal Penelitian Pembelajaran Fisika, 2025)
This study aims to systematically analyze the role of Problem-Based Learning (PBL)-b Student Worksheets in improving 21st-century skills, which include critical, creative, collaborative, and communicative thinking skills in physics learning. The method employed is a literature review, examining 15 relevant national and international articles published between 2015-2025. The results of the study show that the implementation of PBL-based student worksheet is consistently able to improve critical thinking skills through scientific analysis and reflection activities, as well as encourage students' creativity in producing innovative ideas based on contextual problems. In addition, the incorporation of collaboration rubrics and digital-based activities has been proven to strengthen interaction, responsibility, and communication between students in physics learning. The integration of digital collaboration aspects and authentic assessment makes the student worksheet not only a learning medium but also a means of strengthening scientific character and social skills in the 21st century. This research makes an important contribution to the development of PBL-based physics learning tools that are relevant to the challenges of the digital era and can be used as a reference for teachers and curriculum developers to create active, reflective, and collaborative learning.